Pengaruh Pelaksanaan P5 Terhadap Akhlak Pribadi Siswa Pada Kurikulum Merdeka di SMP Negeri 1 Padang Ganting Kab. Tanah Datar - Amirul Akbar Marfit; Puti Andam Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The implementation of the democratic voice project at SMP Negeri 1 Padang Ganting, Tanah Datar Regency which helps students form a profile of faith and devotion to God Almighty and noble character. It can be seen in one of the elements, namely personal morality. This study aims to determine the influence of the implementation of P5 on the development of students' personal morals in the independent curriculum at SMP Negeri 1 Padang Ganting. Using a quantitative method, with a sample of 83 students was determined using the Yamane and Isaac and Micheal formula with an error rate of 5%. Instruments in the form of questionnaires. The analysis technique uses a simple linear regression test and a t-test. The results of the analysis showed that the implementation of P5 had an effect of 39.1% on students' personal morals.The linear regression test produced a constant of 65.324 and a positive regression coefficient of 0.305, which showed that any increase in the implementation of P5 would increase the student's personal morals by 0.305 units. The t-test produced a significance value of 0.000 (<0.05) and Thicount (7.212) greater than that of the Ttable (1.98969), indicating a significant influence. Other factors that affect student morals include the role of teachers, peers, and the family environment.